Immunogenicity of Tumor Initiating Stem Cells: Potential Applications in Novel Anticancer Therapy - Khandekar, Durga; Amara, Suneetha; Tiriveedhi, Venkataswarup (Frontiers in Oncology, 2019)
Tumor initiating stem cells (TISCs) are a subpopulation of tumor cells, which are responsible for cancer relapse and resistance to chemotherapy. The metabolic programs that drive TISC functions are exquisitely unique and finely-tuned by various oncogene-driven transcription factors to facilitate pro-cancerous adaptive challenges. While this change in TISC metabolic machinery allows for the identification of specific molecular targets with diagnostic and prognostic value, these molecules also have a potential immunological application. Recent studies have shown that these TISC-specific molecules have strong antigenic properties enabling naïve CD8+T lymphocytes to differentiate into cytotoxic effector phenotype with anticancer potential. In spite of the current challenges, a detailed understanding in this direction offers an immense immunotherapeutic opportunity. In this review, we highlight the molecular targets that characterize TISCs, the metabolic landscape of TISCs, potential antitumor immune cell activation, and the opportunities and challenges they present in the development of new cancer therapeutics.